Organized Crime - theoretical observations and empirical befunde - Albrecht, Hans-Jörg (2010)
O conceito de crime organizado é marcado por mitos, estimativas e especulações. O conceito estimulou nas últimas décadas a mobilização da Política Criminal a uma incursão nos planos nacional, europeu e internacional, especialmente a partir de duas ordens de fatores. Por um lado, os mercados ilegais de droga na Europa expandiram-se fortemente desde a década de 1970; por outro lado, tem-se o fim da Cortina de Ferro no final da década de 1980, o aumento da migração trans-fronteiriça e a omissão na inspeção das fronteiras.The concept of organized crime is marked through myths, estimates and speculations. The concept has stimulated in the last decades the mobilization of the Criminal Policy to an incursion through national, European and international field, specially due two order of factors. By one side, the illegal markets of drug in Europe expanded itself strongly since the 1970´s decade; on the other hand, it concerns to the fall of the Iron Curtain at the end of the 1980´s decade, the increase of the cross-border migration as well as the oversight in the inspection of the borders